Crack resistance reliability study of CRTS III rail slab on bridge - Jia, Bingliang; Lu, Zhaohui; Zhang, Xuanyi; Zhao, Yangang; ICASP14 (My University, 2023)
Reliability of CRTS III track slab on bridge corresponding to cracking failure mode is analyzed, under multiple loads. A finite element model of CRTS III slab-type ballastless track on bridge is established; considering the uncertainties of train load, temperature gradient, fastener resistance, bridge deflection and the most unfavorable location, the reliability index of CRTS III track slab on bridge corresponding to cracking failure mode is analyzed with the aid of the method of moments, considering both horizontal and vertical directions; and the sensitivity analysis of important random parameters is carried out. It is found that: the cracking reliability indices of the track slab in both horizontal and vertical directions satisfy the specification requirements; the track slab is more likely to crack longitudinally than transversely; the change of load will lead to the change of the most unfavorable position, which makes the changing tendency of reliability index with load show strong nonlinearity.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED